Extracellular Amylase Activity of Amylolytic Bacteria Isolated from Quail’s (Coturnix japonica) Intestinal Tract in Corn Flour Medium - Sjofjan , Osfar; Ardyati, Tri (International Journal of Poultry Science, 2011)
Amylolitic microorganisms have capability of producing amylase which is an important enzyme in industries such as paper, textile and food industries. These microorganisms are found as a normal intestinal microflora in poultry’s digestive tracts including quail (Coturnix japonica), especially with carbohydrates as a most nutrient in their ration. Corn becomes most important feed for quail because it has high energy related to its high amylum content. Amilolytic microorganisms in the digestive tract digest amylum by producing an extracellular enzyme (amylase) which breakdown amylum into simpler molecules facilitating for its absorbtion in the digestive tract. This research aimed to isolate amylolytic bacteria from quail’s digestive tract, to determine their growth and amylolytic activity in corn flour medium. Isolation was done by using Starch Agar medium, then amylolytic activity was indicated based on intensity of clear zone formation in the media and by amylase assay using DNS method in Starch Broth medium. Growth curve and amylase assay was carried out in 2% Corn Flour Broth medium. Data were subjected to analysis of Pearson correlation. The results showed that six isolates called as BAP1, BAP2, BAP3, BAP4, BAP5 and BAP6 were found. BAP6 isolate showed the widest clear zone formation in Starch Agar medium, highest amylase activity and non pathogenic characters. Thus, it was selected and used in further analysis. BAP6 isolate grew well in 2% Corn Flour Broth medium with the highest cell number, 2.2 x 108 CFU/ml at 24 h incubation and the highest amylase activity, 0.0201 Unit at 12 h incubation.